Utility of CD38+ T-cell activation patterns determined by flow cytometry for prediction of classic Hodgkin lymphoma - Kelley Taylor; Sally Ullery; Joe Papiez; Ron Thomason; Ron Lee (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
Objectives: Classic Hodgkin lymphoma (CHL) is not typically diagnosed by routine clinical flow cytometry in most laboratories. While the neoplastic Hodgkin lymphoma/ Reed Sternberg (HRS) cells in CHL may be identified by flow cytometry using special procedures, the methodology used is not common. We observed increased CD38 expression on T-cells compared to Bcells/non-T-cells in cases of CHL compared to normal samples and confirmed our observations in the context of retrospective and prospective analyses. We identified and characterized distinctive features of background non-neoplastic T cells associated with classic Hodgkin lymphoma utilizing common antibodies and analysis methods.  Methods: Cases were retrospectively identified using a search for Hodgkin lymphoma in the Interpretation or comments of reports and prospectively identified with characteristic CD38 expression patterns on non-neoplastic cells and correlated with subsequent morphologic diagnoses.  Results: Retrospective and prospective analyses were identical with respect to predictability of CHL using the pattern analysis described in this paper. Retrospective and prospective analyses predicted the presence of CHL in 82% of cases. There is a statistically significant difference between non-neoplastic T-cells and B-cells/non-T-cells in cases of CHL compared to normal lymph nodes.  Conclusions: There is a distinctive background pattern of non-neoplastic cells associated with most cases CHL (82% in our analyses). There is a statistically significant difference between cases of CHL and normal lymph nodes with respect to the expression of CD38 on non-neoplastic T-cells and B-cells.